A Modified Roger’s Distance Algorithm for Mixed Quantitative–Qualitative Phenotypes to Establish a Core Collection for Taiwanese Vegetable Soybeans - Kao, Chung-Feng; He, Shan-Syue; Wang, Chang-Sheng; Lai, Zheng-Yuan; Lin, Da-Gin; Chen, Shu (Frontiers in Plant Science, 2021)
Vegetable soybeans [Glycine max (L.) Merr.] have characteristics of larger seeds, less beany flavor, tender texture, and green-colored pods and seeds. Rich in nutrients, vegetable soybeans are conducive to preventing neurological disease. Due to the change of dietary habits and increasing health-conscious knowledge, the demand for vegetable soybeans has increased. To conserve vegetable soybean germplasms in Taiwan, we built a core collection of vegetable soybeans, with minimum accessions, minimum redundancy and maximum representation. Initially, a total of 213 vegetable soybean germplasms and 29 morphological traits, were used to construct the core collection. After redundant accessions being removed, 200 accessions were retained as the entire collection, which was grouped into nine clusters. Here, we developed a modified Roger’s distance for mixed quantitative-qualitative phenotypes to select 30 accessions (denoted as the core collection) which had a maximum pairwise genetic distance. No significant difference were observed in all phenotypic traits (p-values>0.05) between the entire and the core collections, except plant height. Compared to the entire collection, we found most traits retained diversities but 7 traits were slightly lost (ranged from 2-9%) in the core collection. The core collection demonstrated a small percentage of significant mean difference (3.45%) and a large coincidence rate (97.70%), indicating representative of the entire collection. Furthermore, large values in variable rate (149.80%) and coverage (92.5%) were in line with high diversity retained in the core collection. The results suggested that phenotype-based core collection can retain diversity and keep genetic variability of vegetable soybeans, providing a basis for further research and breeding programs.